1996
DOI: 10.3109/00016359609003557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral hygiene products containing lactoperoxidase, lysozyme, and lactoferrin on the composition of whole saliva and on subjective oral symptoms in patients with xerostomia

Abstract: This study evaluates the effects of two oral hygiene products containing nonimmunoglobulin antimicrobial agents on whole saliva and on subjective oral symptoms in patients with xerostomia. Twenty patients used a lactoperoxidase-system-containing toothpaste (Biotene) combined with the use of a mouthrinse (Biotene), comprising also lysozyme and lactoferrin, for 4 weeks. Saliva samples were collected at base line, after 4 weeks' use of the products, and at the end of a 4-week washout period. Samples were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 33 publications
2
50
1
Order By: Relevance
“…No major changes occurred in the level of salivary Thiocyanite and Peroxidase activity ( Figure 1 and Figure 2), but there was an increase in salivary pH and also salivary flow rate was notably higher in each group after using Lactoperoxidase products. Our results demonstrate as in Tenovuo et al [27] study that obviously greater benefit of the incorporation of nonimmunoglobulin agents in oral hygiene products is gained by patients who have severe xerostomia (stimulated flow ≤ 0.2ml/min) than in those who have subjective complaints of dry mouth but the salivary flow rate is notably higher. The long-term efficacy of these products in preventing xerostomia remains to be shown.…”
Section: Discussionsupporting
confidence: 85%
“…No major changes occurred in the level of salivary Thiocyanite and Peroxidase activity ( Figure 1 and Figure 2), but there was an increase in salivary pH and also salivary flow rate was notably higher in each group after using Lactoperoxidase products. Our results demonstrate as in Tenovuo et al [27] study that obviously greater benefit of the incorporation of nonimmunoglobulin agents in oral hygiene products is gained by patients who have severe xerostomia (stimulated flow ≤ 0.2ml/min) than in those who have subjective complaints of dry mouth but the salivary flow rate is notably higher. The long-term efficacy of these products in preventing xerostomia remains to be shown.…”
Section: Discussionsupporting
confidence: 85%
“…11 The use of a commercial mouthrinse containing lysozyme, lactoferrin and LP could be useful in xerostomic patients, as suggested by the positive effects observed on subjective oral symptoms in individuals with hyposalivation. 33 A recent 4-day plaque regrowth study, however, showed that such mouthrinse had no plaque inhibitory actions. 34 Similarly, the LP gum we evaluated, although claimed to ''efficaciously reduce plaque'' and ''prevent gingivitis'', provided no plaque control benefits at smooth surfaces.…”
Section: Discussionmentioning
confidence: 96%
“…For years proteins have been used in oral care products to maintain oral health [Lenander-Lumikari et al, 1993;Kirstila et al, 1996;Pedersen et al, 2002;Tenuvuo, 2002], but the addition of proteins to toothpaste is still controversial. Earlier research on these products showed that it was questionable whether these proteins can be immobilized in the acquired pellicle [Hannig et al, 2005].…”
Section: Discussionmentioning
confidence: 99%